Analysis of Histamine Levels in Tuna Loins Product at CV Laut Biru in Sikka Regency - Yohanes D B R Minggo; Angelinus Vincentius (Jurnal Biologi Tropis, 2023)
CV Biru Laut is a Tuna fish company of Sikka regency. The resulting product has gone through several stages of testing, one of which is testing the content of Tuna fish. This study aimed at to determine the histimine content of Tuna Loin products Thunnus albacro CV Laut Biru. The method used was the enzyme linked immunosorbent assay (ELISA) method with qualitative data analysis through a one-way analysis of variance test. The results showed that the value of histamine levels in the CV Laut Biru Tuna Loin Product met the target specifications for histamine levels with the highest test value of 2.66 ppm and the smallest value of 0.54 ppm, while based on the one-way analysis of variance test, there was no difference. The average histamine levels significantly in the test in April 2021.